'We can't be perfect all the time': Life with HIV before antiretrovirals: A narrative analysis of early published stories by women with HIV in the United Kingdom. (February 2022) - Shepherd, Jane
Objectives: The experiences of women like me, diagnosed with HIV before the development of effective antiretrovirals, tend to be neglected and overlooked. Research, policy and services can better serve us if our lived experiences are known and understood within a contextual framework. This small study revisited published personal experience stories by women diagnosed with HIV before 1992 in order to examine what the women said and why. Methods: Due to limited data, a single published collection of 12 stories was chosen, Positively Women: Living with AIDS . Narrative analysis was used to make some overarching sense of identified themes, plots and genres within the women's accounts. This method allows for a deep contextual reading. I adopted an inductive and reflexive approach using my lived experience to weave in contextual detail and analysis. Findings: In their search for sense-making, the women often expressed their life with HIV as transformative. Speaking out and peer support helped women construct a more positive identity and develop strategies for survival that were influenced by ideas contextually situated in an emerging public health crisis. However, women also felt defined and confined by their status, and others spoke of a conflict in living up to an emerging HIV subjecthood that was adherent to wellness regimes, self-improvement and positive thinking. Conclusion: The analysis brings to light some of the contradictions and conflicts within these early HIV narratives. Contextually examining women's narratives from the perspective of lived experience offers new readings and fresh insights into wider cultural narratives that may resonate with today's stories of living with HIV.